2023
DOI: 10.3389/fpubh.2023.1166868
|View full text |Cite
|
Sign up to set email alerts
|

The consumption pattern and perception of using artificial sweeteners among the public in Tabuk region, Saudi Arabia

Sawsan A. S. Alharthi,
Khulud Hassan A. Alaisayi,
Lina Yousef S. Alalawi
et al.

Abstract: BackgroundObesity and weight gain have become major problems worldwide. Thus, several forms of alternative intense sweeteners are extensively used, offering a non-caloric sweet taste. To the best of our knowledge, no research has studied either the consumption pattern or the perception of using artificial sweeteners in Saudi Arabia.ObjectivesOur research aimed to study the usage pattern of such artificial sweeteners in the Tabuk region and estimate the knowledge of and attitudes toward their usage among the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The current study showed that over two-thirds of the women were unaware of any potential adverse effect of LCS, and only a quarter of the women were concerned about the possible adverse effect of LCS on their health as well as their offspring. To our knowledge, no published studies examined the awareness among pregnant women, but the awareness was similar among the general public in a Saudi Arabia study [48] and higher among the adult population in the United Kingdom [49]. Although not statistically significant, awareness about the potential adverse effects of LCS was negatively associated with moderate and habitual consumption patterns in this study.…”
Section: Predictors Of Moderate and Habitual Lcs Consumptionmentioning
confidence: 42%
“…The current study showed that over two-thirds of the women were unaware of any potential adverse effect of LCS, and only a quarter of the women were concerned about the possible adverse effect of LCS on their health as well as their offspring. To our knowledge, no published studies examined the awareness among pregnant women, but the awareness was similar among the general public in a Saudi Arabia study [48] and higher among the adult population in the United Kingdom [49]. Although not statistically significant, awareness about the potential adverse effects of LCS was negatively associated with moderate and habitual consumption patterns in this study.…”
Section: Predictors Of Moderate and Habitual Lcs Consumptionmentioning
confidence: 42%